2020
DOI: 10.1101/2020.10.26.354902
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SETD2 regulates the methylation of translation elongation factor eEF1A1 in clear cell renal cell carcinoma

Abstract: SET domain-containing protein 2 (SETD2) is commonly mutated in renal cell carcinoma. SETD2 methylates histone H3 as well as a growing list of non-histone proteins. To explore SETD2-dependent regulation of the kidney cancer proteome, we performed a systems-wide analysis of protein lysine-methylation and expression in wild type (WT) and SETD2-knock out (KO) kidney cells. We observed decreased lysine methylation of the translation elongation factor eEF1A1. EEF1AKMT2 and EEF1AKMT3 are known to methylate eEF1A1, an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
(3 reference statements)
3
0
0
Order By: Relevance
“…In confirmation of our findings, a recent preprint study also found a negative role for SETD2 in translation regulation in clear cell renal cell carcinoma (ccRCC; Hapke et al 2020). SETD2 inactivating mutations are frequently found in multiple types of cancer, including ccRCC (Dalgliesh et al 2010; Duns et al 2010; Gerlinger et al 2012; Sato et al 2013; Bihr et al 2019), high-grade gliomas (Fontebasso et al 2013), and leukemias (Zhang et al 2012; Zhu et al 2014; Mar et al 2014).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In confirmation of our findings, a recent preprint study also found a negative role for SETD2 in translation regulation in clear cell renal cell carcinoma (ccRCC; Hapke et al 2020). SETD2 inactivating mutations are frequently found in multiple types of cancer, including ccRCC (Dalgliesh et al 2010; Duns et al 2010; Gerlinger et al 2012; Sato et al 2013; Bihr et al 2019), high-grade gliomas (Fontebasso et al 2013), and leukemias (Zhang et al 2012; Zhu et al 2014; Mar et al 2014).…”
Section: Discussionsupporting
confidence: 91%
“…Although ribosomal proteins are common contaminants in co-IP experiments (Pardo and Choudhary 2012), it might be interesting to determine if SETD2 interacts with specific component of the ribosome via the SRI domain, and whether this interaction is relevant for the regulation of protein synthesis by SETD2. In confirmation of our findings, a recent preprint study also found a negative role for SETD2 in translation regulation in clear cell renal cell carcinoma (ccRCC; Hapke et al 2020). SETD2 inactivating mutations are frequently found in multiple types of cancer, including ccRCC (Dalgliesh et al 2010;Duns et al 2010;Gerlinger et al 2012;Sato et al 2013;Bihr et al 2019), high-grade gliomas (Fontebasso et al 2013), and leukemias (Zhang et al 2012;Zhu et al 2014;Mar et al 2014).…”
Section: Discussionsupporting
confidence: 88%
“…In support of our findings, a recent preprint study also found a negative role for SETD2 in protein synthesis regulation in clear cell renal cell carcinoma (ccRCC) (Hapke et al 2020). SETD2 inactivating mutations are frequently found in multiple types of cancer, including ccRCC (Dalgliesh et al 2010;Duns et al 2010;Gerlinger et al 2012;Sato et al 2013;Bihr et al 2019), high-grade gliomas (Fontebasso et al 2013), and leukemias (Zhang et al 2012;Zhu et al 2014;Mar et al 2014).…”
Section: Discussionsupporting
confidence: 88%